2022
DOI: 10.21776/tema.23.1.7-16
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Dewan Komisaris, Komisaris Independen, Dan Kepemilikan Manajerial Terhadap Kinerja Keuangan Perusahaan Di Masa Pandemi Covid – 19

Abstract: The research aims to examine the effect of the variables of the board of commissioners, independent commissioners and managerial ownership on financial performance as measured by Return on Assets (ROA) during the covid-19 pandemic. Board of commissioners and independent commissioners have a role to monitor and provide input for managers to support processes within the company. Managerial ownership is share ownership owned by managerial parties so that they can take part in decision making and encourage activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…These results are in accordance with research conducted by (Pratiwi & Noegroho, 2022), Where it was found that independent commissioners are able to have a negative effect on the company's performance. The proportion of the independent board of commissioners has a negative effect on the company's financial performance.…”
Section: The Influence Of Independent Commissioners On the Company's ...supporting
confidence: 92%
“…These results are in accordance with research conducted by (Pratiwi & Noegroho, 2022), Where it was found that independent commissioners are able to have a negative effect on the company's performance. The proportion of the independent board of commissioners has a negative effect on the company's financial performance.…”
Section: The Influence Of Independent Commissioners On the Company's ...supporting
confidence: 92%
“…Laporan keuangan yang diterbitkan perusahaan juga berkaitan dengan salah satu biaya keagenan, yaitu biaya perikatan. Biaya perikatan adalah biaya yang ditanggung oleh pihak agen dalam rangka mencapai keselerasan tujuan antara prinsipal dengan agen, agar prinsipal tidak dirugikan (Pratiwi & Yulianto, 2016). Laporan keuangan yang dibuat oleh pihak manajemen juga merupakan salah satu bentuk dari penerapan biaya perikatan dalam hubungan keagenan.…”
Section: Teori Sinyalunclassified